Unusual Fungal Infections in Renal Transplant Recipients - Mahesh Eswarappa; P. Vijay Varma; Rakesh Madhyastha; Sujeeth Reddy; M. S. Gireesh; K. C. Gurudev; Vijaya V. Mysorekar; Beena Hemanth (Case Reports in Transplantation)
Fungal infections are an important cause of morbidity and mortality in renal transplant recipients. The causative agent and the risk factors differ depending on the period after the kidney transplant. Also the incidence varies according to the geographical area. We are reporting three cases of fungal infections in renal transplant recipients. Two of them have etiological agents which are common among immunosuppressed patients, but with an atypical clinical presentation, while one of them is a subcutaneous infection caused by a less frequent dematiaceous fungus, Aureobasidium pullulans. These cases highlight how a high index of clinical suspicion and prompt diagnosis is very much essential for better outcome. The emerging fungal infections and paucity of data regarding their management pose a challenge to the transplant physicians.